MENTAL HEALTH PROBLEMS AMONG ADOLESCENT IN BANDA ACEH - Nenty Septiana; Suci Zahratul Liza; Nurul Kamaly (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2025)
Mental health in adolescents is a problem that continues to increase every year and is increasingly concerning. Mental health problems that often occur in adolescents are depression, anxiety, and stress. This condition will have an impact on how well adolescents learn. This study aims to determine the prevalence of mental health problems in adolescents. This study uses a descriptive approach with  94 respondents selected using purposive sampling techniques. Data was collected using a CERDAS application containing the DASS-21 questionnaire. Data analysis used descriptive analysis. The results showed that the level of adolescent depression, anxiety, and stress was in the moderate category with a percentage of 39.4%, 52.1%, and 36.2%. We find that girls scored higher than boys in mental health problems. It is hoped that adolescents can improve mental health literacy and get the right intervention, so that adolescents are more productive in learning and everyday life